Connected Arts Learning: Cultivating Equity Through Connected and Creative Educational Experiences. Issue 1 (March 2022) - Peppler, Kylie; Dahn, Maggie; Ito, Mizuko
This review brings together scholarship from creative educational experiences (CEE) and connected learning to describe a connected arts learning framework, reframing arts education in the 21st century with a focus on connecting youths' interest-driven art making to opportunities through supportive relationships. Such a framework pushes the arts education field to consider outcomes beyond artistic skill acquisition and academic achievement to include a broader range of opportunities, including those civic- and career-related; promote interest development through targeted exposure to new forms of art making; create and implement professional development and programming to emphasize networks and connections; and draw from culturally sustaining practices to bridge connections between spaces for learning. A connected learning lens applied to what we know about high quality arts education sharpens our focus on how CEE can cultivate equity and social/cultural connection for youth.